Diagnostic performance and agreement of auditors for evaluation of computer-aided optical polyp diagnosis: Prospective study - Huang, Felix; Dimbu, Thea Iulia; Rex, Douglas K.; Pohl, Heiko; Hassan, Cesare; Djinbachian, Roupen; Michal, Victoire; Kim, Dong Hyun; Amani, Bilal; Haddouch, Nahlah; Fournier, Sofie; von Renteln, Daniel (Endoscopy International Open, 2025)
Guidelines recommend independent auditing of diagnostic performance for clinical implementation of computer-aided optical polyp diagnosis (CADx). This study evaluated diagnostic performance and interobserver agreement of auditors and offered guidance on conducting CADx audits.Images and videos of all ≤ 5-mm polyps from a large, prospective study with systematic activation of CADx were audited by three expert endoscopists. Experts performed independent, blinded diagnostic review including documentation of confidence level. The primary outcome was sensitivity of audit by three experts for high-confidence adenomas compared with pathology. Secondary outcomes included number of reviewers for optimal CADx auditing and interobserver agreement.Four hundred eighty-seven diminutive polyps were audited (510 patients). Sensitivity was 99.4% (95% confidence interval [CI] 96.0–100) using three experts (Strategy A); 88.7% (95% CI 84.1–92.1) using two experts and one referee (Strategy B); 99% (95% CI 96–99.8), 98.8% (95% CI 95.4–99.8), and 99.4% (95% CI 96.3–100) using two-expert combinations (Strategy C); and 98.2% (95% CI 95.1–99.4), 97.3% (95% CI 94.0–98.9), and 88.9% (95% CI 83.6–92.7) for each expert individually (Strategy D). Among 266 pathology-based adenomas, Strategy A evaluated 160 polyps versus 196, 172, and 170 in Strategy C; and 220, 223, and 207 in Strategy D. Strategy B evaluated all 266 adenomas. Overall interobserver agreement was moderate (kappa 0.52), but very high for high-confidence adenomas (kappa 0.89).Expert audit for evaluating CADx resulted in high sensitivity and interobserver agreement for high-confidence adenomas. Audit by two experts, with a third expert for arbitration, permitted audit of all polyps and effective assessment of CADx within clinical studies.
Keywords: Endoscopy Lower GI Tract; Polyps / adenomas / ...; GI Pathology; Quality and logistical aspects; Quality management